Occurrence of Goitre during Lithium Treatment. Issue 5620 (21st September 1968) - Schou, M.; Amdisen, A.; Jensen, S. Eskjær; Olsen, T.
Abstract : Of 330 patients given lithium for recurrent manic-depressive disorder 12 developed goitre after treatment periods of five months to two years. All the patients remained clinically euthyroid. Pressure symptoms necessitated subtotal thyroidectomy in two patients. In 9 out of 10 patients with goitre, and in two out of seven without goitre study with radioactive iodine showed abnormal findings in iodine metabolism. Discontinuance of lithium led to disappearance of goitres, while thyroid metabolism returned to normal. Thyroxine or desiccated thyroid produced shrinkage of the gland in spite of continued lithium medication.